A bibliometric exploration on intellectual property law practices in businesses - Yasin, Nurul Ibtisyami; Siman, Aslina; Mohamad Dasuki, Norhafizah; Atan, Nur Atika (Human Resource Management Academic Research Society, 2024)
In today's business environment, intellectual property (IP) plays a vital role in fostering innovation and competitiveness. With businesses facing growing complexities in IP law, understanding the scholarly landscape has become essential. This study offers a bibliometric analysis of intellectual property law practices in businesses, examining key trends, influential contributors, and emerging themes. Given the vast body of literature on this topic, this analysis helps scholars, practitioners, and policymakers navigate important works and evolving trends. Using the Scopus database, the study analyzes authorship patterns, citation counts, publication trends, and thematic clusters through co-citation and keyword cooccurrence analyses. The research seeks to reveal key contributors, collaborative networks, and thematic concentrations in intellectual property law and business practices discourse. By assessing the evolution of research trends and intellectual impact, this study aims to provide a comprehensive overview of the intellectual structure of the field. The findings will guide future research, foster interdisciplinary collaboration, and support policymakers in shaping effective intellectual property laws related to businesses. This analysis ultimately aims to advance knowledge and innovation at the intersection of intellectual property and business practices.